Meningkatkan Kemampuan Hubungan Interpersonal Melalui Layanan Bimbingan Kelompok Teknik Sosiodrama pada Siswa Kelas IX-1 SMP Negeri 1 Praya - Zehni Zehni (JUPE : Jurnal Pendidikan Mandala, 2019)
In the preliminary study conducted in IX-1 grade students of Junior High School No. 1 Praya, Central Lombok, NTB, it was found that approximately 68% of the students having low and average interpersonal relation skill. Classroom observations also showed that students tend to be passive during the lesson, quiet, less collaboration in group, and lack of interaction among peers. Guidance and Counselling teachers attemp to conduct a classroom study in guidance and counselling using sociodrama technic group guidance, as an attempt to improve students’ interpersonal relation skill. This study is aimed to to find out how the implementation of sociodrama technic group guidance can improve students’ interpersonal relation skill based on the needs of IX-1 grade students in junior high school No. 1 Praya. The study design of this classroom action research used Kemmis and Mc Taggrat model, Kemmis used self reflection spiral system, consisted of planning, acting, observating, reflecting, and replanning. Based on the result of this action research in guidance and counselling and discussion in two cycles, it can be conclued that sociodrama technic group guidance can improve IX-1 grade students’ interpersonal relation skill in junior high school No. 1 Praya. The result was found from the increasing score of students’ interpersonal relation skill before and after the implementation of sociodrama technic group guidance. The conclusion was made based on the analysis result of two times post-test and observation data during the two cycles of this research. The result indicated that 8 students who used to have a low interpersonal relation skill could achieve a higher category of interpersonal relation skill, there were 2 and 6 students having average category of interpersonal relation skill, and there was an increasing trend in interpersonal relation skill among the studets after the sociodrama technic group guidance was implemented